Synthesis and mesomorphic behaviour of highly ordered liquid crystalline D-A-D-type Carbazole-TPD-Carbazole. (2nd August 2020) - Hu, Guang; Kitney, Stuart P.; Harrison, William; Lambert, Brian
ABSTRACT: Novel symmetrical carbazole-thieno[3, 4 -c ]pyrrole-4, 6-dione-carbazoles (Carbazole-TPD-Carbazole) were designed and synthesised as donor–acceptor-donor (D-A-D) materials. The correlations between their molecular structures, differing only in the length of the symmetrical terminal linear alkyl chains attached to a carbazole-TPD-carbazole moiety in the molecular core, and their mesomorphic behaviour, transition temperatures, energy levels and band gaps were studied for a potential use of these D-A-D materials as hybrid organic semiconductors for plastic electronics applications.